ADAPTASI MORPHO-PHYSIOLOGI NILAM (Pogostemon ) TERHADAP CEKAMAN KEKERINGAN: Morpho-physiological Adaptation of Patchouli(Pogostemon) to Drought Stress - Agus Sadono (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2020)
Patchouli (Pogostemon) can live in dry land and produce atsiri oil. Dry land often,experiencing drought but Patchouli can survive , Adaptability patchouli for life in drought stress condition interesting to ivestigate the cause. The aim of this experiment looking for morpho-physiological characteristics of patchouli varieties adaptive to drought stress condition. The experiment with A Randomized Completely Design with four replicates was used in the trial. Five varieties of patchouli namely Aceh Merah, Lhokseumawe,Tapak Tuan, Sidikalang and Girilaya were transplanted into 30 x 15 x 90 cm wood pot and treated with less water to initiate drought stress after transplanted, all pots were saturated with water (until 100% field capacity), and then treated with nowater addition up to 120 days after transplanting (DAT). Parameters observed were: growth and production biomass and proline content in leaf. The results showed that the highest growth and biomass production components were performed by Girilaya andfollowed by Tapak Tuan varieties. While Sidikalang variety was the lowest in productivity. Maximum length of root, fresh weight of root, and proline content in leaf were also found at Girilaya and followed by Tapak Tuan. Data collection on the growth, production, and morpho-physiological characteristics in relation to adaptation level to drought stress indicated that Girilaya, a Java patchouli group (Pogostemon haeyanus Benth), was the most tolerant among varieties tested. While among the Aceh patchouli group (Pogostemon cablin Benth) Tapak Tuan was the most tolerant variety.Keywords : Adaptation, Patchouli, morpho-physiological characteristic, drought stress